An Islamic Perspective of Organizational Controls and Performance Evaluation (American Journal of Islam and Society, 1992)
An organizational performance evaluation is one part of a largermanagement control process involving complex relationships between variablesat the social, the organizational, and the individual levels. Thephilosophy, criteria, and methods used in performance evaluation varygreatly between different social and organizational cultures. In this paper,we address the issue from the perspective of a specific religion,’ Islam,and the culture which it has created, Islamic culture (IC), and compare itwith a secular culture (SC). Improvement and effectiveness in secular organizations(SO) are driven by economic considerations: while Islamicorganizations (IO) are required to look beyond such considerations. Thesupremacy of economic considerations limits an SO’S vision to thme materialisticaspects which provide the domain for deriving individual, social,and organizational goals and, at some point, everything must add up todollars and cents. An SO also derives transitory goals from economic considerations,for its organizational process emphasizes utilitarian and objectiveprinciples which state that profit maximization (or optimization) ispossible and also provides the criteria by which to measure success. In anIO, utilitarian objectives are allayed by spiritual needs, where the ideal is“reasonable profit,” and where there are sanctions against excessive profits.By definition, an organization is a purposive human system with purposesand goals which organizes and ptocesses material and human resomesfor the generation of output. For an SO, output is determined bysocial and economic goods and services, and a system’s success is measuredby its output’s quality and cost efficiency. The system’s reward isthe profit earned. Most of its output and reward measures are necessarilyquantitative and extrinsic in natute. An individual is, like any other partof that system, a supportive element vis-his the production of goods andservices. Thus the individual is part of a process driven by economic andquantitative criteria of success, one which has no room for hisher ownmoral and ethical standards. In other words, religious standards play noformal role in the SO management process.